(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Etiology of hypertension plays a key role for the management of hypertension and prevention of hypertension. Sympathetic over activity and reduced parasympathetic control are triggering factors for the high blood pressure. Obesity is considered in daily clinical practice as one of the main health problems widely distributed over the world. Furthermore, hypertension is main cause of ischemic heart disease and cerebrovascular accidents. To assess the effect of obesity on cardiovascular responses in patient sample with SBP, DBP and Heart Rate. Materials and methods: This is a cross sectional study. A Selected patients from those visiting the Outpatient of Cardiology Department of Shaheed Tajuddin Ahmad Medical College Hospital who suffer from primary hypertension and randomly distributed into two groups: Obese hypertensive and Hypertensive without obesity. A third group who are non-hypertensive obese patients also randomly selected from a group of patients who are visiting outpatient of medicine for viral diseases like acute self-limiting illness. A control group of seemingly healthy individuals involved doctors and a health staff in the hospital. Results: A highly significant of the mean systolic blood pressure of patient with hypertension and obese hypertensive patients than of both the obese and control “groups [p<0.05]. A highly significant mean diastolicblood pressure of patient with hypertension and obese hypertensive-patients than that of both the obese and control groups [p < 0.05] highly significant mean heart rate of patients with hypertension and obese patients with hypertension than that of both obese and control groups [p < 0.05]”. Also, after extreme workout and 15 min. following rest there was significantly different in hemodynamic reaction after extreme workout and 15 minutes following rest between groups. Conclusion: After extreme workout and 15 minutes after rest a significant difference was found among the groups. JCMCTA 2022 ; 33 (2) : 126-132